Removal of Zinc and Copper from Aqueous Solutions by Electrocoagulation Technology Using Iron Electrodes - Bazrafshan, Edris; Hosein Mahvi, Amir; Ali Zazouli, Mohammad (Asian Journal of Chemistry, 2011)
The aim of this study is to evaluate the batch electrocoagulation for the removal of zinc and copper from synthetic wastewater using iron electrodes with bipolar configuration. The effects of several working parameters, such as pollutant concentration (5, 50 and 500 mg L-1), pH (3, 7 and 10), applied voltage (20, 30 and 40 V), reaction time (15, 30, 45 and 60 min), COD and turbidity were evaluated. The results indicated that the most effective removal capacities of studied metals (> 99.99 %) could be achieved when the applied voltage was kept equal 40 V. In addition, it is found that an increase in the applied voltage enhanced the speed of the treatment significantly. However, simultaneous increase of electrode and energy consumption was observed. Also consumed energy decreased with increase in zinc and copper concentration. Finally, the results demonstrated the technical feasibility of electrocoagulation as a reliable technique for removal of heavy metals from aqueous environments.